Tree growth influenced by warming winter climate and summer moisture availability in northern temperate forests. (25th January 2020) - Harvey, Jill E.; Smiljanić, Marko; Scharnweber, Tobias; Buras, Allan; Cedro, Anna; Cruz‐García, Roberto; Drobyshev, Igor; Janecka, Karolina; Jansons, Āris; Kaczka, Ryszard; Klisz, Marcin; Läänelaid, Alar; et al.
Abstract: The role of future forests in global biogeochemical cycles will depend on how different tree species respond to climate. Interpreting the response of forest growth to climate change requires an understanding of the temporal and spatial patterns of seasonal climatic influences on the growth of common tree species. We constructed a new network of 310 tree‐ring width chronologies from three common tree species ( Quercus robur, Pinus sylvestris and Fagus sylvatica ) collected for different ecological, management and climate purposes in the south Baltic Sea region at the border of three bioclimatic zones (temperate continental, oceanic, southern boreal). The major climate factors (temperature, precipitation, drought) affecting tree growth at monthly and seasonal scales were identified. Our analysis documents that 20th century Scots pine and deciduous species growth is generally controlled by different climate parameters, and that summer moisture availability is increasingly important for the growth of deciduous species examined. We report changes in the influence of winter climate variables over the last decades, where a decreasing influence of late winter temperature on deciduous tree growth and an increasing influence of winter temperature on Scots pine growth was found. By comparing climate–growth responses for the 1943–1972 and 1973–2002 periods and characterizing site‐level growth response stability, a descriptive application of spatial segregation analysis distinguished sites with stable responses to dominant climate parameters (northeast of the study region), and sites that collectively showed unstable responses to winter climate (southeast of the study region). The findings presented here highlight the temporally unstable and nonuniform responses of tree growth to climate variability, and that there are geographical coherent regions where these changes are similar. Considering continued climate change in the future, our results provide important regional perspectives on recent broad‐scale climate–growth relationships for trees across the temperate to boreal forest transition around the south Baltic Sea. Abstract : A tree‐ring network from European beech, Scots pine and oak trees from around the south Baltic Sea was compiled to examine the relationship between tree growth and climate. Our findings indicate tree growth is influenced by warming winter climate and summer moisture availability in northern temperate forests. Furthermore, spatial analysis suggests that there are geographical patterns in similar growth responses to climate and that these responses can be unstable through time.